METODE USULAN ANALISA MATERIAL BALANCE P/Z TAK BERDIMENSI UNTUK SUMUR GAS BERTENAGA PENDORONG BOTTOM WATER DRIVE - Imanuddin, Hanif
Material balance is often used for the determination of initial gas in place of a reservoir. P/Z vs. Gp method usually use to estimate the value of a IGIP in gas production field. However, in reality, this method is often used for the field that does not have a driving mechanism, especially strong water but this method is used in very weak water drive, so the effect of driving mechanism can be neglected. With the water influx from the aquifer, there is a tendency curve P / Z make some deviation from the initial conditions. So later, IGIP value obtained does not represent the original condition. Therefore, in this study, the curve of P / Z vs. Gp was modicated from material balance equation by including parameters of water influx and water production. For validating the proposed method, we analyze and compare the value of IGIP that obtained from this method with value of IGIP from reservoir model. In sensitivity analysis for every change of aquifer rock property parameters, the equation P / Z dimensionless by calculating the maximum value of the compressibility gives maximum error only 5% of IGIP reservoir models, whereas the sensitivity analysis for reservoir parameters, especially initial porosity reservoir, IGIP maximum error is 1.6%. Moreover, this study discusses the comparison between proposed method with the previous method, Havlena Odeh, and applying technic of proposed methods in the field case.